Beef steers production in integrated crop-livestock systems: pasture management under different sward heights - Wesp, Cristiane (2015)
The aim of this study was to evaluate the effects of different grazing intensities on forage production and animal performance of yearling steers kept under permanent grazing in an integrated crop-livestock system. The treatments consisted of areas with sward heights of 10; 20; 30 and 40 cm, and one treatment with no grazing. The pastures were of bristle oat (Avena strigosa Schreb.) and annual ryegrass (Lolium multiflorum Lam.)   following soybean (Glycine max (L.) Merr.). The variables forage mass, forage allowance and residual straw showed a positive and linear fit to the increasing sward height (P≤0.0001). Average daily gain of steers displayed a quadratic response (P = 0.0017),  being optimal with increases in grazing height up to values of near 30 cm, showing a weight gain per animal of approximately 1.0 kg day-1. A similar response was seen for live weight at slaughter and carcass characteristics (P≤0.0305). The results suggest that sward heights close to 30 cm provide greater individual gains, due to the increase in forage available to each animal and the better quality of the consumed forage without compromising the residual straw destined for the following crop.